The Symbolic Meaning of the Momasoro Traditional Procession in the Lauje Community of Ogoansam Village, Indonesia’s Palasa District - Fadila, Ayu; Mardiah, Mardiah (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
This study aims to explore the symbolic meaning of the Momasoro tradition practiced by the Lauje tribe in Ogoansam Village. A qualitative descriptive method was employed to conduct the research. Data collection involved multiple techniques, including observation, interviews, documentation, listening, recording, and note-taking. The research utilized two primary data sources: first-hand symbolic meanings of the Momasoro tradition gathered through observations and interviews. The analysis process followed three steps: data reduction, data presentation, and conclusion drawing. The findings revealed a total of 10 symbolic elements integral to the Momasoro tradition. These include boats, offerings, ketupat (rice cakes), chicken eggs, sticky rice, cucur cakes, gong and drum musical instruments, large knives, mantras, and white chickens. Each element carries specific cultural and spiritual significance within the tradition.